Social media advertising platforms: a cross-cultural study - Zotos, Yorgos; Chatzithomas, Nikolaos; Boutsouki, Christina; Hatzithomas, Leonidas (My University, 2014)
The advent of social media tools has led to a new era in advertising theory and practice. However, scant amount of research addresses the ways in which social media are used in different countries to convey corporate image. The purpose of the present study is to increase our understanding of the adoption of social media for external communication purposes. Based on a content analysis of 250 websites of the “Fortune 500” companies in the USA and 265 websites of the “Strongest Companies in Greece”, the study performs a cross cultural comparison of issues and trends in the use of social media advertising techniques in the USA and Greece. The findings show that US advertisers tend to use social media for advertising purposes more frequently than their Greek counterparts. In fact, the use of social media as an element of the promotional mix is still at an early phase in Greece, since Greek practitioners seem to have underestimated the importance of this source of corporate communications. Though significant differences between the U.S.A. and Greece seem to exist, there are, also, some critical similarities between the two environments. In particular, business to consumer (B2C) enterprises focus mainly on the use of Twitter and Facebook, while business to business (B2B) emphasize YouTube and RSS. Moreover, it seems that high tech companies are pioneers of the use of Web 2.0 tools for advertising purposes, while traditional firms seem to lag behind such practices. The present study contributes to the relevant literature by analyzing the use of social media in a cross cultural environment. In that manner, significant strategies for more effective exploitation of social media advertising both in countries that are early adopters (as the U.S.A.) and countries that are late adopters of innovations (as Greece) emerge.
Keywords: Social media; Cross-cultural; U.S.A.; Greece; Corporate communications